Evaluation of Solid Medical Waste Management in Bogor Regional Public Hospitals - Khansa, Silvia; Kusumayati, Agustin; Susanna, Dewi; Sinaga, Uli Tiarma (Kesmas, 2023)
Healthcare facilities generate medical waste. If not properly managed, medical waste may damage the environment and spread diseases. Many hospitals in Indonesia do not adhere to medical waste management regulations. This study aimed to evaluate the management of solid medical waste at four public hospitals in Bogor District, Indonesia. A case study design was used to obtain a comprehensive description of the solid medical waste management activities inthe hospitals. Data were collected through direct observations, interviews, and document reviews. This study revealed that the medical waste generated in allhospitals was infectious, pathological, pharmaceutical, chemical, and cytotoxic, totaling approximately 4,000-12,000 kg. Hospitals A, B, C, and D fulfilled the Regulation of the Indonesian Ministry of Environment and Forestry No. P56 of 2015 criteria, achieving compliance rates of 77%, 83.78%, 83.3%, and 86.48%, respectively. However, several activities of the hospitals did not meet the standards for waste reduction, segregation, on-site transport, temporary storage, and human resource quality. It is important that hospitals establish comprehensive and compliant medical waste management systems.